Inventur : Werke aus der Sammlung Herbert. (Köln : Walther König, 2006)
Andre, Carl ; Anselmo, Giovanni ; Art & Language ; Baldessari, John ; Broodthaers, Marcel ; Brouwn, Stanley ; Buren, Daniel ; Bustamante, Jean-Marc ; Cadere, Andre ; Darboven, Hanne ; Dibbets, Jan ; Fabro, Luciano ; Gilbert & George ; Graham, Dan ; Judd, Donald ; Kawara, On ; Kelley, Mike ; Kippenberger, Martin ; Kosuth, Joseph ; LeWitt, Sol ; Long, Richard ; Merz, Mario ; Mucha, Reinhard ; Nauman, Bruce ; Paolini, Giulio ; Penck, A.R. ; Pistoletto, Michelangelo ; Richter, Gerhard ; Schütte, Thomas ; Smithson, Robert ; Toroni, Niele ; Vercruysse, Jan ; Vermeiren, Didier ; Weiner, Lawrence ; West, Franz ; Wilson, Ian ; Zobernig, Heimo
boek
Keywords: Herbert, Annick; Herbert, Anton